PECULARITIES OF HЕART RATE DISTURBANSES IN NEWBORNS WITH PERINATAL HYPOXIA - Batman, Yu.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Negativeinfluenceofperinatalhypoxia  is evident in development of hemodynamic and metabolic disorders in myocardium. One of the leading pathophysiological mechanism of arrhythmia development in neo-natal period is heart rate neurogen stimulation disturbance which leads to electrical myocardium instability. It were analyzed  results of investigation of 74 babies with clinical features of  cardiovascular system lesions manifested in arrithmia. Changes in sings of heart function vegetative regulation in newborn with peri-natal hypoxia mean that thre is increasing of tonus of sympatheticic part of vegetative nervous system. Possible  ethiopathogenetic factor  of hypersympathicotonia is ante- and intranatal stress.